دور القضاء الإداري في رقابة العملية الإنتخابية: رقابة مرحلة الترشح نموذجا - عباسي, سهام; جديدي, نهلة (University of Eloued جامعة الوادي, 2018)
The role of the administrative judiciary in monitoring the electoral process, as the electoral process as a safety valve to protect the rights and freedoms of the basic individuals and determine the extent of the rule of law, most electoral systems in the world resort to the extension of administrative control over this process, including Algeria, This intervention is the role of the administrative judiciary in protecting the process - the electoral process - in the various electoral electoral entitlements, which put the stage of candidacy as a model for this role through analyzing this stage at the legal level regulating the legislative framework. Judicial activated for those texts.
الملتقى الدولي الثامن: التوجيهات الحديثة للقضاء الإداري ودوره في إرساء دولة القانون 06-07 مارس 2018 جامعة الوادي
Keywords: الإنتخابات، الرقابة، القضاء الإداري، الترشح; Elections, censorship, administrative judiciary, candidacy